The Roles of Market Concentration and Diversity in Exploring the Nexus between Financial leverage and Firm Performance - M. Almajali; W. M.Z. Wan Abdullah; H. M. Zia-Ul-Haqc (Финансы: теория и практика)
The purpose of the study is to determine the relationship between financial leverage and the financial performance of companies in the insurance industry in Jordan, taking into account the influence of market concentration and product diversity. It analyzes data from 20 Jordanian insurance companies over 15 years (2005-2019). The study reveals a positive connection between financial leverage and insurance company profitability, with product diversification enhancing this relationship. Initially, market concentration had a negative impact on return on equity, but product diversification turned it into a positive influence. Additionally, the study highlights the positive mediating role of market concentration in the financial leverage-financial performance relationship. These findings have practical implications for insurers, emphasizing the need for diversified product portfolios and effective financial leverage strategies in a competitive market. This research contributes to understanding capital structure dynamics in emerging markets, specifically in the Jordanian insurance sector, by providing empirical evidence of the mediating and moderating effects of market concentration and product diversity.